Analysis of meteorological drought pattern during different climatic and cropping seasons in Bangladesh - Alamgir, Mahiuddin (Blackwell Publishing Inc., 2015)
Drought is one of the most frequent natural disasters in Bangladesh which severely affect agro-based economy and people's livelihood in almost every year. Characterization of droughts in a systematic way is therefore critical in order to take necessary actions toward drought mitigation and sustainable development. In this study, standardized precipitation index is used to understand the spatial distribution of meteorological droughts during various climatic seasons such as premonsoon, monsoon, and winter seasons as well as cropping seasons such as Pre-Kharif (March-May), Kharif (May-October), and Rabi (December-February). Rainfall data collected from 29 rainfall gauge stations located in different parts of the country were used for a period of 50 years (1961-2010). The study reveals that the spatial characteristics of droughts vary widely according to season. Premonsoon droughts are more frequent in the northwest, monsoon droughts mainly occur in the west and northwest, winter droughts in the west, and the Rabi and Kharif droughts are more frequent in the north andnorthwest of Bangladesh. It is expected that the findings of the study will support drought monitoring and mitigation activities in Bangladesh.